Lagrangian flow effects on phytoplankton abundance and composition along filament-like structures. (November 2020) - Hernández-Carrasco, Ismael; Alou-Font, Eva; Dumont, Pierre-Antoine; Cabornero, Andrea; Allen, John; Orfila, Alejandro
Abstract: Influence of frontal dynamics on phytoplankton distribution and composition was studied combining in situ observations and Lagrangian computations from altimetry satellite derived currents. Four transects during the SHEBEX cruise (May 2015) over the Western Mediterranean were examined identifying a region with high spatial variability in the dynamical and biogeochemical properties. The dynamical situation unraveled from the Lagrangian analysis is dominated by filaments originated by an anticyclonic–cyclonic eddy interaction that organize the transport, modifying the biogeochemical properties of the water column and shaping the satellite derived surface Chlorophyll a (chl a ) distribution. The properties of the water column have been analyzed in relation to the dynamical properties of the filaments showing that local variation of the mixed layer and nutricline depths are correlated with the spatial variability of finite size Lyapunov exponents. Furthermore, the composition of phytoplankton community was studied regarding the path-accumulated properties of the flow during the formation of the filaments. In this regard new metrics accounting the Lagrangian evolution of the turbulent and topological properties of the flow along fluid parcel trajectories have been developed. Here we provide observational evidence that fluid parcels associated with high Lagrangian turbulent kinetic energy and Lagrangian positive vorticity host higher presence of larger pennate diatoms (i.e. Pseudo-nitzschia spp). Our findings indicate that the combination of these diagnostics provides an improved description of the turbulent dynamics showing that the Lagrangian properties of the flow have important biological consequences for phytoplankton to high ecological levels. Highlights: Lagrangian vorticity (LV) improves the dynamical description of eddies. Eddy–eddy interaction induces filaments with high Lagrangian turbulent energy (LEKE). Lagrangian coherent structures locally modify the mixed layer and nutricline depths. Higher abundance of diatoms observed at filaments with higher values of LV and LEKE.